Analysis of a FANCE Splice Isoform in Regard to DNA Repair. Issue 19 (25th September 2015) - Bouffard, Frédérick; Plourde, Karine; Bélanger, Simon; Ouellette, Geneviève; Labrie, Yvan; Durocher, Francine
Abstract: The FANC-BRCA DNA repair pathway is activated in response to interstrand crosslinks formed in DNA. A homozygous mutation in 1 of the 17 Fanconi anemia (FA) genes results in malfunctions of this pathway and development of FA syndrome. The integrity of this protein network is essential for good maintenance of DNA repair process and genome stability. Following the identification of an alternatively splice isoform of FANCE ( F anconi an emia c omplementation group E ) significantly expressed in breast cancer individuals from high-risk non-BRCA1/2 families, we studied the impact of this FANCE splice isoform (FANCEΔ4) on DNA repair processes. We have demonstrated that FANCEΔ4 mRNA was efficiently translated into a functional protein and expressed in normal and breast cancer cell lines. Following treatment with the crosslinking agent mitomycin C, EUFA130 (FANCE-deficient) cells infected with FANCEΔ4 were blocked into G2/M phase, while cell survival was significantly reduced compared with FANCE-infected EUFA130 cells. In addition, FANCEΔ4 did not allow FANCD2 and FANCI monoubiquitination, which represents a crucial step of the FANC-BRCA functional pathway. As observed for FANCE wild-type protein, localization of FANCEΔ4 protein was confined to the nucleus following mitomycin C treatment. Although FANCEΔ4 protein showed interaction with FANCE, FANCEΔ4 did not support normal function of FANCE protein in this pathway and could have deleterious effects on FANCE protein activity. We have demonstrated that FANCEΔ4 seems to act as a regulator of FANCD2 protein expression level by promoting its degradation. This study highlights the importance of an efficient regulation of alternative splicing expression of FA genes for proper DNA repair. Graphical Abstract: Highlights: A novel alternative splicing event of the FANCE gene has been characterized. FANCEΔ4 cannot support the activation of the FANC-BRCA pathway and DNA repair. FANCEΔ4 tends to have a negative impact on FANCD2 protein expression. Three sequence variations can potentially modulate FANCEΔ4 / FANCE expression ratio.